2012
DOI: 10.2903/j.efsa.2012.2593
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the re‐evaluation of mixed carotenes (E 160a (i)) and beta‐carotene (E 160a (ii)) as a food additive

Abstract: The Panel on Food Additives and Nutrient Sources added to Food provides a scientific opinion reevaluating the safety of mixed carotenes [E 160a (i)] and β-carotene [E 160a (ii)] when used as food colouring substances. Mixed carotenes [E 160a (i)] and β-carotene [E 160a (ii)] are authorised as food additives in the EU and have been evaluated previously by the JECFA the latest in 2001 and by the SCF in 1997 and 2000. Both Committees established an Acceptable Daily Intake (ADI) of 0-5 mg/kg bw/day. In this opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 114 publications
(263 reference statements)
0
17
0
Order By: Relevance
“…There is similarly no evidence that conversion of β-carotene to vitamin A contributes to vitamin A toxicity, even when β-carotene is ingested in large amounts. Standard toxicological tests, including teratogenic, mutagenic, and carcinogenic assays, have been performed on β-carotene without any evidence of harmful effects, as reviewed in ref (47).…”
Section: Results and Discussionmentioning
confidence: 99%
“…There is similarly no evidence that conversion of β-carotene to vitamin A contributes to vitamin A toxicity, even when β-carotene is ingested in large amounts. Standard toxicological tests, including teratogenic, mutagenic, and carcinogenic assays, have been performed on β-carotene without any evidence of harmful effects, as reviewed in ref (47).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nowadays, the exposure to these compounds is extensive and widespread in the food industry, especially through use of carrot, tomato and sweet potato powders. The estimated range of exposure to natural OxBC (1-22 mg per serving) is comparable to the level of safe intake of β-carotene (<15 mg/d) that results from the regular consumption of the foods in which β-carotene occurs naturally (5-10 mg/d), in addition to food additives and food supplements (European Food Safety Authority, 2012a). Consumption of common tomato-based products results in exposure to even higher levels of natural oxidized carotenoids (Burton et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, several longer chain β-apocarotenoid cleavage products were identified as possible toxicity candidates in both types of simulated oxidized β-carotene product mixtures (Alija et al, 2005; Alija et al, 2004; Eroglu et al, 2012; Kalariya et al, 2009; Marques et al, 2004; Yeh and Wu, 2006). The physiological relevance of these in vitro studies has been questioned in a review in 2012 of the safety of β-carotene by an EFSA Panel (European Food Safety Authority, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The safety of mixed carotenes and β-carotene was re-evaluated by the European Food Safety Authority (EFSA) in 2012 (EFSA ANS Panel, 2012a). EFSA concluded that the use of (synthetic) β-carotene and mixed β-carotenes obtained from palm fruit oil, carrots and algae as food colour is not of safety concern, provided the intake from this use as a food additive and as food supplement is not more than the amount likely to be ingested from the regular consumption of the foods in which they occur naturally (5-10 mg/day).…”
Section: Discussionmentioning
confidence: 99%